Antifungal activity of nano-composite films based on Poly Lactic Acid - Mahya Shafiee Nasab (Nanomedicine Research Journal, 2019)
Objective(s): Nanocomposite active packaging systems were used to prepare antimicrobial and antifungal properties. This study was to investigate the physical and antimicrobial activity of prepared films against three types of aflatoxin producing fungi Aspergillus Flavus. Material and methods: For investigating the effect of antibacterial nano-covers, the direct contact of 0, 1%, 3% and 5% zinc oxide nanoparticles was contaminated with standard strains of three types of Aspergillus Flavus (PTCC 5004), Aspergillus Parasiticus (PTCC 5286) and Aspergillus Parasiticus (PTCC5018) provided. Pistachios were coated by edible films then peroxid index gradient were measured during the time for coating Pistachios containing different concentrations of 0, 1 and 3% of “nano-ZnO”. Then coating pistachios were preserved inside sealed Polyethylene bags for six months and the effect of preventing fungal growth during the time were investigated. Results: The study of antifungal properties of films on three Aspergillus spp. showed that all four percent of nano zinc oxides in this study has inhibitory effect by increasing the percentage of nano-materials significantly (P <0.05). Poly lactic acid edible films Containing 5% nanoparticles has appropriate coating with anti-oxidation agent. Nano-coating Pistachios were observed any growth of mold, however, growth was observed in all control samples. Conclusion: Poly lactic acid films containing nano-zinc oxide show a high potential for antifungal pistachios packaging applications to enhance the shelf life of this products.